2009
DOI: 10.1007/s11270-009-0254-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality Assessment of Watershed Associated with Animal-Based Agriculture in Santa Catarina, Brazil

Abstract: Environmental problems many times could evolve when manure-containing pathogens are distributed into an open environment with no effort made to reduce the content of pathogens or limit their movement in the environment. Wind, surface flow, and subsurface flow can all carry enough pathogens to receiving waters to exceed water quality standards. This study was conducted to assess the microbiological quality of water associated with animal-based agriculture in the sub-basin of Pinhal River located in the rural ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Bacteria in stormwater runoff from developed and undeveloped land uses often result in high levels in downstream receiving waters (Edwards et al 1997;Crowther et al 2002;Sigua et al 2010). Increased bacteria levels can cause management concerns in terms of public and ecological health and can affect the ability of areas to achieve intended recreational uses (Jones 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria in stormwater runoff from developed and undeveloped land uses often result in high levels in downstream receiving waters (Edwards et al 1997;Crowther et al 2002;Sigua et al 2010). Increased bacteria levels can cause management concerns in terms of public and ecological health and can affect the ability of areas to achieve intended recreational uses (Jones 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Salmonella spp. in biofertilizer has already been described (Fongaro et al 2014), and also the contamination of water bodies caused by land use (Sigua et al 2009). Schneider et al (2009) isolated E. coli from Suruvi river (surface water) and wells located near the river (groundwater), and the results showed that from the 205 E. coli isolates, more than a half were resistant to antibiotics (63 % from groundwater and 52 % from surface water).…”
Section: Discussionmentioning
confidence: 95%
“…The relatively high levels of prevalence of pathogenic bacteria during the rainy season suggest high influx of sewage, soil leaching and flooding as well as good survival capabilities of these microorganisms to changing hydrographic parameters (Mohamed et al 2008). Sigua et al (2010) too have demonstrated that a positive relationship exists between the variability of faecal contamination levels and agricultural cover. This substantiates the mounting risk of enhanced contamination occurring rapidly during the rainy season as agricultural cover increases.…”
Section: (Meningitis and Skin Infections) Andmentioning
confidence: 95%
“…Pathogenic bacteria which may cause serious problem for human health have been studied mostly for their survival in the aquatic ecosystem (Sood et al 2008;Nagvenkar and Ramaiah 2009;Harakeh et al 2006;Servais et al 2007;Sigua et al 2010). Servaais et al (2007) studied faecal contamination of the main rivers of the Seine watershed (Seine, Marne, Oise rivers) and found high levels of microbiological pollution when compared to European guidelines for bathing waters.…”
Section: (Meningitis and Skin Infections) Andmentioning
confidence: 99%